High Cycling Performance Li‐S Battery via Fenugreek Gum Binder Through Chemical Bonding of the Binder with Polysulfides in Nanosulfur@CNFs Cathode - Mo, Yu‐Xue; Wu, Yi‐Jin; Yin, Zu‐Wei; Ren, Wen‐Feng; Gao, Zhen‐Guang; Zhang, Peng‐Fang; Lin, Jin‐Xia; Zhou, Yao; Li, Jun‐Tao; Huang, Ling; Sun, Shi‐Gang (ChemistrySelect (Weinheim), 2020)
The dissolution and diffusion of lithium polysulfides are one of the main intrinsic bottlenecks in the development of lithium‐sulfur (Li−S) batteries with long term cycling stability. Appropriate binders could play a key role of anchoring the lithium polysulfides in S‐cathode through strong chemical bonds, thus boosts the electrochemical performance of Li−S battery. Herein, we report a new binder (fenugreek gum, FG) that has enhanced significantly the cycling performance of Li−S batteries with S@CNFs composite as cathode. The Li−S cell with FG binder delivers a large initial capacity of 900 mAh g−1 at 2 C, and a reversible capacity retention of 45.6 % after 1300 cycles, superior to the cycling performance of Li−S cell with conventional PVDF or previous reported guar gum (GG) binder. This enhancement in cycling performance of Li−S batteries could be attributed to the formation of the S−O and Li−O bonds between the O‐relevant functional groups in the binder and the polysulfides in S‐cathode as manifested by XPS data of the discharged and charged electrodes. Furthermore, the tensile strain rate of the FG binder is as high as 32 %, which can effectively restrain the volume expansion of the S‐cathode during the discharge/charge process and ensure the integrity of the electrode. In Li−S system, the electrode binders play a significant role in improving the electrode performance by restraining the dissolution and diffusion of lithium polysulfides during cycling. Herein, a new natural and nontoxic fenugreek gum binder, which has abundant oxygen‐containing functional groups and hightensile strain rate, is demonstrated to effectively restrain the volume expansion of the S‐cathode during the discharge/charge process and ensure the integrity of the electrode, thus greatly enhancing the electrochemical performance of Li−S batteries using S@CNFs as the electrode materials.